THE SORPTION CAPACITY OF ERYTHROCYTE MEMBRANES IN EXPERIMENTAL EMPHYSEMA - Пономаренко, О.Б.; Коржов, В.І.; Жадан, В.М.; Liskina, I.V.; Мельник, О.О. (World of Medicine and Biology, 2016)
The sorption capacity of red blood cells changes in papain experimental emphysema was studied. The presence of pulmonary emphysema in the experimental animals was confirmed by the morphological studies. Changes of erythrocytes sorption capacity can be considered as an indicator of damage to the membranes. Rats with experimental pulmonary emphysema had decreased the sorption capacity of red blood cells, regardless of the period of observation.